2014
DOI: 10.3390/v6041473
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Juquitiba Virus in Oligoryzomys fornesi from Brazilian Cerrado

Abstract: The Juquitiba virus, an agent of Hantavirus Cardiopulmonary Syndrome, is one of the most widely distributed hantavirus found in South America. It has been detected in Oligoryzomys nigripes, Akodon montensis, Oxymycterus judex, Akodon paranaensis in Brazil and in O. nigripes, Oryzomys sp. and Oligoryzomys fornesi rodents in Argentine, Paraguay and Uruguay. Here, we report the genomic characterization of the complete S segment from the Juquitiba strain, isolated from the lung tissues of O. fornesi, the presumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…18 Furthermore, the occurrence of JUQV-like infection in two different genera of hosts suggests a potential adaptation of this genotype to genetically distinct rodent species, as previously observed in the central and southern regions of Brazil, where distinct rodent species, A. montensis, Akodon paranaensis, Oligoryzomys mattogrossae (fornesi), Oligoryzomys Judex, and Thaptomys nigrita have been identified as being naturally infected with JUQV. [19][20][21][22] In this study, the cursor grass mouse was the most abundant species identified and has adapted to exist in primary and secondary forests, especially in the transition area between Atlantic Forest and Cerrado areas in southeastern Brazil. It is a generalist species that occurs near human habitation, as does the black-footed pygmy rice rat (O. nigripes).…”
Section: Resultsmentioning
confidence: 89%
“…18 Furthermore, the occurrence of JUQV-like infection in two different genera of hosts suggests a potential adaptation of this genotype to genetically distinct rodent species, as previously observed in the central and southern regions of Brazil, where distinct rodent species, A. montensis, Akodon paranaensis, Oligoryzomys mattogrossae (fornesi), Oligoryzomys Judex, and Thaptomys nigrita have been identified as being naturally infected with JUQV. [19][20][21][22] In this study, the cursor grass mouse was the most abundant species identified and has adapted to exist in primary and secondary forests, especially in the transition area between Atlantic Forest and Cerrado areas in southeastern Brazil. It is a generalist species that occurs near human habitation, as does the black-footed pygmy rice rat (O. nigripes).…”
Section: Resultsmentioning
confidence: 89%
“…Additionally, based on serologic tests and genetic analyses, researchers detected a Juquitiba‐like hantavirus circulating in two non‐related rodent species ( Oligoryzomys nigripes and Oxymycterus nasutus ) in Maldonado, Uruguay, which indicates the occurrence of spillover infection or a host‐switching event [Delfraro et al, ]. Recently, researchers described the JUQV in tissues of Oligoryzomis fornesi in the Cerrado region, that could be interpreted as incidental, but the capacity of these viruses to adapt to a new reservoir has been more frequent than what was previously thought [Guterres et al, ]. Even though ARAV is considered the most virulent hantavirus in Brazil [Figueiredo et al, ] and the majority of samples that were analyzed here segregated with the ARAV group, it was observed that all three deaths were caused by JUQV.…”
Section: Discussionmentioning
confidence: 99%
“…event [Delfraro et al, 2008]. Recently, researchers described the JUQV in tissues of Oligoryzomis fornesi in the Cerrado region, that could be interpreted as incidental, but the capacity of these viruses to adapt to a new reservoir has been more frequent than what was previously thought [Guterres et al, 2014]. Even though ARAV is considered the most virulent hantavirus in Brazil [Figueiredo et al, 2009] and the majority of samples that were analyzed here segregated with the ARAV group, it was observed that all three deaths were caused by JUQV.…”
Section: Discussionmentioning
confidence: 99%
“…Hantaviruses are transmitted horizontally within reservoir populations, either directly through aggressive interactions or indirectly through the environment [18] , [19] , [20] . In the latter situation, infection occurs when susceptible individuals inhale infectious particles released into the environment, resulting in spillover events or cross-species transmission [21] , [22] , [23] , [24] . Within the hantavirus transmission flow, the prevalence and distribution of infection in rodent hosts are influenced by a range of factors.…”
Section: Environmental Determinantsmentioning
confidence: 99%